The new international economic order: a view from the socialist corner - Leon Zurawicki (Intereconomics, 1982)
The attitude towards development aid of the socialist countries of Eastern Europe, who recently made themselves conspicuous once more by their absence from the Cancún summit, has come under increasing attack from the Third World. Our author takes a critical look at the socialist countries' position and explains why it would serve their own interests to take a different stand.
Keywords: 330